Girls. The complete fourth season [videorecording (DVD)] - Dunham, Lena, 1986- (HBO Home Box Office, 2015)
In the fourth season the girls are tentatively edging toward maturity as they take on new personas in new worlds. As the season begins, Hannah leaves New York to attend the prestigious Iowa Writers' Workshop in the hopes of becoming a more serious writer, while confronting uncertainty in her relationship with Adam. Meanwhile, back in New York, Marnie pursues a music career while balancing her professional and romantic relationship with Desi; Shoshanna graduates and begins interviewing for jobs.